(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article discusses the use of the medicinal product Decacan in medicine and the mechanism of action. Decacan accumulates in the cytoplasmic membrane (SPM) of the microbial cell and binds to the phosphatide groups of membrane lipids, disrupts the SPM of microorganisms, and has an antimicrobial and antifungal effect.